How end-user participation in Financial Management Information Systems development engenders a sense of system ownership in municipalities: A case in South Africa - Gcora-Vumazonke, Nozibele Pansy (Department of Information Systems, 2022)
Background: The public sector in South Africa has long been concerned with poor performance in financial management in municipalities. The Auditor-General who has a constitutional mandate to audit government departments highlighted challenges in financial management facing the municipalities. The challenges include lack of compliance with the legislation of municipal financial management, weak audit outcomes, financially unqualified financial statements, mismatch in produced financial statements, missing reports regarding performance, incomplete disclosure in financial authorisation and unauthorised and waste expenditure. To overcome these challenges, the government introduced the Financial Management Information Systems (FMIS) to municipalities in South Africa to support budget preparation and implementation, accounting and reporting, performance monitoring and auditing and evaluation. However, FMIS have not reached widespread use and in the majority of municipalities required re-implementation. Employees are concerned that FMIS are not aligned with their work processes. Lack of sense of ownership towards FMIS is the contributing factor to end-users being reluctant to use FMIS. It was noted that end-users of FMIS were not given a chance to take control and contribute to the development of FMIS for their municipalities. Objective: Previous research posits that the degree of end-user's sense of ownership towards a system that they use in the workplace positively correlates to their level of involvement in the development process of the system. Employees in government departments such as municipalities are not usually involved or participate in the system development process. Sense of ownership towards the system is expected to arise when end-users participate in the system development process of the system. End-users may perceive that they have influence and control during the development of the system and thereby develop a sense of ownership about the system when it is ready for use. The study, therefore, investigated how end-user participation in system development engenders a sense of ownership among end-users of FMIS in municipalities. Method: The study was qualitative, deductive, followed the interpretive research epistemology and drew on a theory of psychological ownership as a theoretical lens, to analyse how end-user participation in FMIS development engenders a sense of ownership. A case study of the Western Cape Province focusing on two local and two district municipalities was considered as a representation of a South African context. Data was collected through semi-structured interviews, observations of end-users during co-design sessions of FMIS development and document analysis. Thematic data analysis was appropriate for the study. Findings: Findings showed that end-users were excluded through the waterfall system development model used for FMIS development. The FMIS development was a top-down approach in which strategic decisions regarding the implementation of FMIS were made from the executive top management of the National and Provincial Treasury departments. The communication about the development was between National Treasury, Provincial Treasury and the system development team. Although end-users were provided training before using the system, they were concerned that the systems were not aligned with their work processes. It was evident that end-user participation in project initiation, system requirements specifications and system design specifications phases could enable end-users to gain a sense of ownership in the form of a sense of responsibility through problem-solving and decision-making, meaningfulness through collective learning during participation and locus of control through shared leadership. End-users revealed that the more they contribute to the development, they learn new skills, feel psychologically empowered and boost their confidence towards FMIS. End-users emphasised that shared leadership during end-user participation is likely to have an influence on how the system is developed to suit work processes. However, findings showed that end-user participation in organisations with complex structures such as municipalities could be hindered by a myriad of factors. Standardisation and lack of stakeholder collaboration, complex job-design and leadership-style approach across tiers of government have been stated by end-users as factors that may hinder the effectiveness of end-user participation in system development in municipalities. Originality/contribution: The theoretical contribution of the research emerges from the use of the theory of psychological ownership to investigate end-user participation to engender an end-user's sense of ownership towards FMIS. There is a lack of evidence-based studies in developing countries focusing on the end-user perspectives regarding factors affecting poor uptake of information systems in the public sector. To address this gap, this study made a descriptive contribution to the concept of a sense of ownership. There is a dearth of studies examining how end users of information systems in government departments in developing countries can be empowered through a sense of ownership to enhance the use and acceptance. In response to this research gap, this study focuses on the concept of end-user participation and contributes to the body of IS knowledge by examining the end-user participation approach as a systems development strategy to engender a sense of ownership to end-users of information systems in government departments.